2014
DOI: 10.1002/bjs.9384
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of predictors of post-thyroidectomy hypocalcaemia

Abstract: Perioperative PTH, preoperative vitamin D and postoperative changes in calcium are biochemical predictors of post-thyroidectomy hypocalcaemia. Clinical predictors include female sex, Graves' disease, need for parathyroid autotransplantation and inadvertent excision of PTGs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

27
491
15
45

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 557 publications
(639 citation statements)
references
References 111 publications
27
491
15
45
Order By: Relevance
“…According to a study of 100 cadaveric thyroid glands32, 38.2 per cent of the parathyroid vessels were considered at risk of damage during standard thyroidectomy; the authors reported that the four parathyroid glands were at risk in 5 per cent of the subjects. These results32 provide an anatomical explanation for the consistent reporting of a small proportion of patients with definitive hypoparathyroidism in most registry‐based or multicentre studies1, 33, 34. Hypothetically, ICG angiography could identify the vascular supply of parathyroid glands at risk of damage during dissection.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…According to a study of 100 cadaveric thyroid glands32, 38.2 per cent of the parathyroid vessels were considered at risk of damage during standard thyroidectomy; the authors reported that the four parathyroid glands were at risk in 5 per cent of the subjects. These results32 provide an anatomical explanation for the consistent reporting of a small proportion of patients with definitive hypoparathyroidism in most registry‐based or multicentre studies1, 33, 34. Hypothetically, ICG angiography could identify the vascular supply of parathyroid glands at risk of damage during dissection.…”
Section: Discussionsupporting
confidence: 57%
“…Postoperative hypoparathyroidism is currently the most common complication of total thyroidectomy1, and there is a need for a reliable tool that can accurately predict whether a patient will develop hypocalcaemia1, 14, 15. Currently available methods to evaluate parathyroid function are based on measurements of calcium16, 17 and PTH2, 6, 7, 18, 19, 20 levels at different time points after thyroidectomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its incidence depends on the technical difficulty of the procedure and expertise of the surgeon. Permanent hypocalcemia, defined as hypocalcemia for more than 6 months after thyroidectomy, is reported in 1-10% of patients (5,6). Reducing the rate of hypoparathyroidism is essential for improving the quality of life, as postoperative hypocalcemia can result in prolonged hospitalization and multiple clinic visits, neuromuscular symptoms, the need for life-long calcium and vitamin D supplementation, and long-term complications, such as cerebral, vascular, ocular, and renal damage (7)(8)(9)(10)(11).…”
Section: Vascular Anatomy Of the Parathyroid Glands (Pgs) And Its Impmentioning
confidence: 99%
“…Recent systematic review indicated that perioperative parathyroid hormone (PTH) level, preoperative vitamin D, and postoperative changes of calcium were biochemical predictors of postoperative hypocalcemia (7). Of these factors, postoperative PTH was considered as the most useful predictor of hypocalcemia.…”
Section: Introductionmentioning
confidence: 99%